2019
DOI: 10.1016/j.aca.2019.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Early sepsis diagnosis via protein and miRNA biomarkers using a novel point-of-care photonic biosensor

Abstract: Sepsis is a condition characterized by a severe stage of blood-infection often leading to tissue damage, organ failure and finally death. Fast diagnosis and identification of the sepsis stage (sepsis, severe sepsis or septic shock) is critical for the patient´s evolution and could help in defining the most adequate treatment in order to reduce its mortality. The combined detection of several biomarkers in a timely, specific and simultaneous way could ensure a more accurate diagnosis. We have designed a new opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 27 publications
0
55
0
1
Order By: Relevance
“…Coupling of this technique with enzyme-linked immunosorbent assay (ELISA) has been achieved [128], demonstrating the feasibility of this approach. Optics comprised of interferometric biosensors coupled with immunoassay have been constructed, using antibodies to CRP and IL-6 which are linked directly to the sensor chip, thereby removing the requirement of a second, labelled antibody [129]. Although the concept in this study was to provide multiplex measurement of CRP and IL-6, the results suggested that there was some degree of cross reactivity and the authors concede that the use of a second antibody and reverting to the more traditional sandwich antibody format may be necessary.…”
Section: Point-of-care Testing (Poct) For Sepsismentioning
confidence: 99%
“…Coupling of this technique with enzyme-linked immunosorbent assay (ELISA) has been achieved [128], demonstrating the feasibility of this approach. Optics comprised of interferometric biosensors coupled with immunoassay have been constructed, using antibodies to CRP and IL-6 which are linked directly to the sensor chip, thereby removing the requirement of a second, labelled antibody [129]. Although the concept in this study was to provide multiplex measurement of CRP and IL-6, the results suggested that there was some degree of cross reactivity and the authors concede that the use of a second antibody and reverting to the more traditional sandwich antibody format may be necessary.…”
Section: Point-of-care Testing (Poct) For Sepsismentioning
confidence: 99%
“…Among precursors of modern biosensor technologies are such diagnostic platforms as quantitative and semi-quantitative test systems for identifying specific antigens [9] and antibodies [10] as well as gene amplification products [11][12][13][14] based on latex agglutination and lateral flow immunoassay (LFIA). In the past decades, these tools have been successfully used to diagnose and identify molecular markers of infection, and they have not lost their biomedical significance today [10,11,13,15] (Figure 1).…”
Section: Lateral Flow Immunoassay (Lfia) As Simplified Formats Of Modmentioning
confidence: 99%
“…It is interesting that the evolution of sensory technologies developed in parallel with the emergence of diagnostic platforms for the lateral flow immunoassay (LFIA), which in our time are considered as simplified formats of modern biosensors [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, interferometric SPR can achieve LODs of Δn ≈ 10 −8 , but this sensitivity is only achieved over 5 × 10 −5 RIU, unless advanced designs are used that are costly, cumbersome, and not suitable for POC applications 7 . An alternative and intrinsically simpler approach is to exploit the phase sensitivity of goldnanohole arrays 9 , which have shown LODs on the order of 10 −4 RIU with a detection limit for proteins in tens of µg mL −1 range 10 . The goal of our work, which is targeted at POC applications, is to maintain simplicity while improving both the sensitivity and the dynamic range.…”
Section: Introductionmentioning
confidence: 99%